A Tool for Suggesting Ayurvedic Remedies from Curated and Classified Clinical Trial Reports - Raj, Sariga; p, Priya (International Journal of Engineering and Technology, 2018)
It requires great effort to search through huge number of published articles that provide information we need. Therefore it is necessary to find a solution that helps researchers in gaining accurate and deep understanding about diseases. Thus drug discovery and drug repurposing are gaining significance with the current onics tools. Traditional Medical practices like Ayurveda needs to be more visible to practitioners with evidence based approach. The clinical trials conducted have to be shared with the world for attaining the very philosophy of Ayurveda.. This paper presents a survey on various text mining technologies developed to classify theories and literature pertaining to the clinical observations of practitioners and suggests a possible solution to match a patientâ€™s symptoms.Â Â